THE EVOLUTION OF EUROSCEPTIC RHETHORICS IN THE EU:BRITISH INFLUENCE AFTER BREXIT AND NATIONAL SPECIALTIES (Вісник: Міжнародні відносини, 2025)
B a c k g r o u n d.                  After Brexit, Euroscepticism has become an increasingly visible part of the European political mainstream. For a certain period following the British referendum, it employed rhetoric suggesting that this scenario might be repeated in other EU member states such as Germany, France, and Italy. Appeals to such a course of events have raised concerns about the continuation of the European Union’s disintegration under the slogans of restoring national sovereignty, regaining control over borders, etc.M e t h o d s.        The study applies a qualitative narrative analysis to identify key milestones in Eurosceptic parties’ attitudes toward the idea of leaving the European Union (following the Brexit example) or, at the very least, limiting European integration.R e s u l t s.          It was found that, despite ties with the initiators of Brexit, local European conservatives and Eurosceptics have gradually adjusted their messaging regarding opposition to European integration, favouring a “soft” form of Euroscepticism — not rejecting EU membership outright but advocating for reducing Brussels’ influence or changing the EU’s political agenda. A restraining factor has been warnings about the negative economic and domestic political consequences of leaving the EU, as illustrated by the British example, and in some cases, appeals to potential external influences (primarily from Russia) and manipulation of European public opinion.C o n c l u s I o n s.                The external political, social, and security environment encourages changes in initial positions on leaving the EU; however, this does not automatically translate into a positive attitude toward European integration itself or solidarity with EU values. There is a pragmatic, rather than value-based, interest in expanding cooperation within the European continent — in the context of shared challenges, particularly the Russian–Ukrainian war.
Keywords: Euroscepticism; European integration; nationalism; post-Brexit